2016
DOI: 10.1016/j.urology.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-Methionine on the Risk of Phosphate Stone Formation

Abstract: The present findings show that L-methionine effectively decreases urinary pH and the risk of struvite and calcium phosphate stone formation in healthy subjects. Hypercalciuria is not expected to occur at physiological doses of L-methionine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
0
20
0
4
Order By: Relevance
“…A recent study in healthy adults showed that the administration of 1500 mg/day l -methionine clearly decreases diurnal urinary pH ( Figure 1 ) [ 31 ]. Urinary sulfate excretion, a direct marker for the metabolism of l -methionine, and ammonium excretion, which reflects the increase in net acid production, increased significantly after l -methionine administration.…”
Section: Net Acid Excretion and Urinary Phmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in healthy adults showed that the administration of 1500 mg/day l -methionine clearly decreases diurnal urinary pH ( Figure 1 ) [ 31 ]. Urinary sulfate excretion, a direct marker for the metabolism of l -methionine, and ammonium excretion, which reflects the increase in net acid production, increased significantly after l -methionine administration.…”
Section: Net Acid Excretion and Urinary Phmentioning
confidence: 99%
“… Diurnal variation in urinary pH during a 24-h period in healthy individuals under controlled, standardized conditions before (control, blue line) and after receiving 1500 mg/day l -methionine (red line) (M ± SEM) (* p < 0.05) [ 31 ]. …”
Section: Figurementioning
confidence: 99%
“…The oral composition studied contains both urine acidifier and crystallization inhibitors, such us L-methionine (an essential amino acid recommended by the EAU Guidelines on Urolithiasis with acidifier properties for the treatment of infectious stones) and phytin (a phytate salt with demonstrated inhibitory properties of calcium stones) as active components. L-methionine directly reduces/acidifies urine pH [15,16], whereas crystallization inhibitors [17] decrease the risk of renal stone formation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The oral composition studied contains both urine acidifier and crystallization inhibitors, such us Lmethionine (an essential amino acid recommended by the EAU Guidelines on Urolithiasis with acidifier properties for the treatment of infectious stones) and phytin (a phytate salt with demonstrated inhibitory properties of calcium stones) as active components. L-methionine directly reduces/acidifies urine pH (15,16), whereas crystallization inhibitors (17) decrease the risk of renal stone formation (18,19).…”
Section: Introductionmentioning
confidence: 99%